BANK OF TEETH: AT THE SERVICE OF ENDODONTIC TEACHING IN GRADUATION AT THE SOVEREIGN HEALTH FACULTY OF PETROLINA IN PERNAMBUCO - Sophia Motta Araújo, Agnes; Caroline Ribeiro Lacerda, Anne; Amanda da Silva Lima Amorim, Érica; Sanchez da Cunha, Fernanda; Rocha Tavares, Larissa; Cavalcante Carneiro, Laís; de Souza Pereira, Malvina; Laura Uchôa Alencar Modesto, Maria; Natágoras Alves de Albuquerque, Marcone; Noemi Granja Rodrigues, Séfora (Health and Society, 2023)
Endodontics is the dental specialty responsible for the study of the dental pulp, the entire system of root canals and periapical tissues, as well as the diseases that affect them. for professional training. The purpose of this article was to address didactic-scientific issues regarding the use of human teeth in laboratory teaching and pre-clinical training in the discipline of Endodontics in Dentistry and to report the experience of the Faculdade de Saúde de Petrolina-SOBERANA with the Human Teeth Bank project , implemented as an academic extension project (PEA), with a multidisciplinary character, resulting from the work of the students, under the guidance of the guiding professor. Of the 10 students eligible for this research, 9 used teeth provided by BioBancoVasf, with a 90% success rate. With this, it is concluded that BioBancoVasf is of paramount importance for the university, valuing the tooth as an organ and enabling the execution of more effective practical studies.